2020
DOI: 10.3390/ijerph17051669
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Physical Activity Reduces the Risk of Renal Progression in Hypertensive Patients

Abstract: Physical activity has long been associated with chronic diseases. However, the association between physical activity and renal progression in hypertensive patients remains unclear. This study investigated the relationship between the level of physical activity and renal function in hypertensive patients. We analyzed 3543 patients with hypertension. Data on patients’ demographic characteristics, comorbidities, physical activity, and lifestyle characteristics were collected via questionnaires. An estimated glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, we calculated the METs and categorized into three levels of physical activity based on IPAQ ( 20 ), including low ( n = 1,379), moderate ( n = 1,411), and vigorous ( n = 40). To investigate the relationship between different levels of physical activity and vascular HMOD, we conducted multivariate logistic regressions after adjustment for confounders, and the results indicated that only the resulting OR for peripheral artery disease was significantly negatively associated with a moderate-to-vigorous level of physical activity (OR: 0.74, 95% CI: 0.60–0.93, p = 0.009) relative to a low level of physical activity ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we calculated the METs and categorized into three levels of physical activity based on IPAQ ( 20 ), including low ( n = 1,379), moderate ( n = 1,411), and vigorous ( n = 40). To investigate the relationship between different levels of physical activity and vascular HMOD, we conducted multivariate logistic regressions after adjustment for confounders, and the results indicated that only the resulting OR for peripheral artery disease was significantly negatively associated with a moderate-to-vigorous level of physical activity (OR: 0.74, 95% CI: 0.60–0.93, p = 0.009) relative to a low level of physical activity ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Weekly walking activity was evaluated by standard questionnaires based on the International Physical Activity Questionnaires-short form (IPAQ, including how many days spent on walking at least 10 min at a time and walking duration time) ( http://www.ipaq.ki.se ), which has been validated and widely used in many clinical trials ( 18 20 ). In subgroup analysis, walking duration was classified into four groups (non-walking activity; 10–29 min/day; 30–59 min/day; ≥1 h/day), and walking frequency were categorized into <3 days/week and ≥3 days/week, with reference to the Korean National Health and Nutrition Examination Surveys (KNHANES) ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Change in physical activity in our study was not associated with kidney function decline in patients with manifest CVD. Previous studies have found higher physical activity to be associated with decreased risk of rapid eGFR decline 11 . Physical inactivity indirectly influences the risk of CKD through the development of obesity, diabetes and hypertension, which were all adjusted for in our main analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, progressive loss of kidney function can be diminished by a number of interventions, including prescription of a RAS‐inhibitor, 6 SGLT2‐inhibitor, 7 adequate control of known risk factors such as diabetes mellitus and hypertension, and lifestyle interventions, including smoking cessation, 8 weight loss, 9 lower alcohol consumption 10 and physical exercise 11 . Reduced intake of sodium has also been shown to lower kidney function decline 12 .…”
Section: Introductionmentioning
confidence: 99%